الأمن الاجتماعي لأطفال العراق دراسة في حالة الطفولة العراقية في ظل احتلال داعش - مجيد علي, نورا (Journal of College of Education, 2020)
The study focused on identifying the social conditions of the Iraqi child during the ISIS occupation of Iraqi cities in 2014, including the city of Mosul. The researcher adopted the social survey method by adopting the questionnaire through a sample of families in the city of Mosul to reveal the study goals, and the study reached a set of results, the most important of which are:• Both Iraqi children suffered from ISIS terrorist occupation of Iraqi cities.• Children in Mosul were affected by ISIS terrorist practices of killing, torture and violence towards members of society.• The majority of the children in the city were afflicted with mental and physical illnesses due to ISIS practices towards them or towards a member of their family.• Many families are still suffering from the sick conditions of their children due to the injustice, violence and abuse that they face from ISIS.
Keywords: الأمن ، الأمن الاجتماعي ، الطفل